Pengaruh model problem based learning terhadap peningkatan kemampuan pemecahan masalah matematis siswa: Studi meta-analisis - Gunawan, Iwan; Amalia, Rizki; Syaban, Mumun; Nurhayati, Lina (Karoteh Utama, 2022)
This study aims to analyze the influence of the application of problem-based learning models on students' mathematical problem-solving abilities based on the research results. The method used is a meta-analysis by analyzing the research results in articles published nationally relating to applying problem-based learning models to increase students' problem-solving skills at the high school level. The samples analyzed were thirteen articles from nationally published journals published in the 2015-2020 range at the junior and senior high school levels, which discussed increasing students' mathematical problem-solving abilities. The instrument is a coding sheet or coding data that filters data and journal information. Based on the overall effect size analysis results, it is obtained that the average effect size value is in a large category. The findings from the analysis also prove that the problem-based learning model for mathematical problem-solving abilities is influential and effective in terms of educational level, subject matter and learning media used. The result shows that in this study, the problem-based learning model is more effectively used in improving mathematical problem-solving skills than conventional learning models.